P170 Humoral immune responses to COVID-19 vaccines are reduced in patients with severe asthma. (11th November 2022) - Rupani, H; Edwards, D; Richards, J; Chaudhuri, R; Smith, S; Jackson, DJ; Hearn, A; Edwards, M; Johnston, S; Moyses, H; Kurukulaaratchy, RJ; Haitchi, HM; et al.
Abstract : Background: Patients with severe asthma (SA) may be at higher risk of severe COVID-19 (C-19) illness. C-19 vaccines aim to reduce number and severity of infections. Patients with SA are often treated with maintenance oral corticosteroids (mOCS) and/or biologics- it is unknown if vaccines will generate the same protective responses in patients with SA on such therapies. Aims: To compare magnitude and range of post-vaccination (PV) antibody responses (IgG) in patients with SA on biologics, mOCS or high-dose inhaled corticosteroids (ICS) with healthy controls (HC) without asthma. To review temporal trends in PV IgG in patients with SA Methods: The Virtus finger-prick quantitative C-19 antibody test was used to detect IgG levels 16–24 weeks post second-dose of the C-19 vaccine (123 AstraZeneca, 56 Pfizer, 5 Moderna). PV IgG levels were also measured in a subset of patients 6 weeks PV. IgG>0.2 AU was considered positive with range: very high >1.25 AU, high 0.751–1.25 AU, medium 0.401–0.75 AU and low 0.201–0.4 AU. SA was defined as per ATS/ERS criteria. Results: PV IgG results were obtained from 127 patients with SA (84 on biologics, 13 mOCS and 46 ICS) and 57 HC. After adjusting for age, significantly fewer people with SA compared to HC had a positive PV IgG result (81% vs 95% p=0.016). Compared to HC (1.24 AU), lower median IgG levels were seen in patients on high dose ICS (1.02 AU, p=0.033) and mOCS (0.40 AU, p=0.017). Patients on biologics had high or very high IgG levels (omalizumab n=25, 0.80 AU; mepolizumab n=25, 1.07 AU; benralizumab n=34, 1.11 AU). Paired temporal measurements in 37 SA patients showed regression coefficient -0.005 (95%CI -0.006, -0.003) and can be interpreted as IgG decreases, on average, by 0.15 AU per month. Conclusion: Overall, a higher proportion of patients with SA had a negative PV IgG level after receiving 2 doses of a C-19 vaccine. This was mainly seen in patients on mOCS while biologic use was not associated with reduced humoral antibody response. These results reinforce the need for booster vaccines in SA, especially in those on mOCS.